Effects of different factors on fly ash-based functional soil and its oat grass cultivation - Liu, Tengteng; Han, Fenglan; Xing, Zhibing; Wang, Jiaqi; Dong, Xiongwei; An, Changcong (Frontiers in Plant Science, 2022)
Using fly ash as the main matrix for plant ecological restoration is effective for constructing a sustainable and ecological environment. The relevant properties of functional soil change due to different factors. Based on the orthogonal experiment of functional soil and the pot experiment of oat grass, fly ash was used as the matrix material for functional soil. Afterward, MX (large granules dispensing certain nutrients), SJJXWS (a water-retaining agent), and AF (a nutrient conditioner) additives were added to study the physical, chemical, and agronomic properties of functional soil, such as the emergence rate and weight of plants. The results showed the high pH and conductivity of functional soil, implying alkaline soils with high salinity. The contents of organic matter and available phosphorus and potassium were relatively high, indicating its high nutrient content. Further analysis revealed that the MX was the key factor affecting functional soil’s electrical conductivity and evaporation, and thus, the corresponding plant emergence rate, plant weight, and other related indicators. The influence of each factor on the corresponding plant emergence rate, plant weight, and other indicators of functional soil was arranged in the order of MX (large granules dispensing certain nutrients), SJJXWS (a water-retaining agent), and AF (a nutrient conditioner). The optimum additive ratio in functional soil was 0.45 t·hm-2 of MX, 0.12 t·hm-2 of SJJXWS, and 1.65 t·hm-2 of AF. The results of this study provide a theoretical basis for further development of functional soil for ecological cycle restoration purposes.